2016
DOI: 10.1111/mmi.13314
|View full text |Cite
|
Sign up to set email alerts
|

A novel Zn2Cys6 transcription factor BcGaaR regulates D‐galacturonic acid utilization in Botrytis cinerea

Abstract: D-galacturonic acid (GalA) is the most abundant monosaccharide component of pectin. Previous transcriptome analysis in the plant pathogenic fungus Botrytis cinerea identified eight GalA-inducible genes involved in pectin decomposition, GalA transport and utilization. Co-expression of these genes indicates that a specific regulatory mechanism occurs in B. cinerea. In this study, promoter regions of these genes were analysed and eight conserved sequence motifs identified. The Bclga1 promoter, containing all thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 52 publications
3
32
0
Order By: Relevance
“…Phenotypic characterization of mutants lacking the GA-regulator in both B. cinerea and A. niger has shown that GaaR is required for growth on GA (Alazi et al 2016;Zhang et al 2016). Expression analysis in both fungi confirmed that GaaR is required for the induced expression of GA-responsive genes.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…Phenotypic characterization of mutants lacking the GA-regulator in both B. cinerea and A. niger has shown that GaaR is required for growth on GA (Alazi et al 2016;Zhang et al 2016). Expression analysis in both fungi confirmed that GaaR is required for the induced expression of GA-responsive genes.…”
mentioning
confidence: 78%
“…), and Dothideomycetes [Zymoseptoria (Mycosphaerella), Aureobasidium, and Cochliobolus spp.] (Zhang et al 2016). Synteny analysis of 17 species belonging to four classes of Pezizomycetes (Eurotiomycetes, Leotiomycetes, Sordariomycetes, and Dothideomycetes) revealed a strong conservation of the genomic clustering of gaaR and gaaX orthologs ( Figure 5 and Table S5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several conserved zinc binuclear cluster transcription factors required for the regulation of genes encoding enzymes important for the transport and utilization of the component saccharides have been identified. In Botrytis cinerea and A. niger, the utilization of galacturonic acid, the most abundant pectin component, is regulated by GaaR (Alazi et al, 2016;Zhang et al, 2016), while in A. niger and A. nidulans, the utilization of rhamnose and arabinose, two minority pectin components, is regulated by RhaR and AraR, respectively (Battaglia et al, 2011a(Battaglia et al, , 2011bGruben et al, 2014;Pardo and Orejas, 2014) (Fig 1 and Table 1). The identification of additional transcription factors may be necessary to fully elucidate the regulation of pectin utilization.…”
Section: Primary Transcription Factorsmentioning
confidence: 99%
“…Previous studies, mostly in the highly pectinolytic fungi Aspergillus niger  ( A. niger ) and Botrytis cinerea ( B. cinerea ), have shown that individual sugars liberated from pectin by secreted enzymes, such as d -GalA, l -Ara, l -Rha and d -Gal, or their respective metabolic derivatives have an inducing potential for the corresponding gene products [2527]. Recently, transcription factors (TFs) that are conserved across fungi and that mediate the response to some of these monosaccharides have been identified: TRC1 and RhaR for l -Rha in Pichia stipitis ( P. stipitis ) and A. niger , respectively [28, 29], GaaR for d -GalA in B. cinerea [30] and Ara1 for l -Ara in Magnaporthe oryzae ( M. oryzae ) [31]. While identified in different fungi, these TFs have in common that they are responsible for regulating a subset of genes involved in the degradation of a particular pectin domain or pectic polysaccharide: HG for GaaR, the RG-I backbone for RhaR, and the arabinan side chains of RG-I (or hemicellulosic arabinan) for Ara1.…”
Section: Introductionmentioning
confidence: 99%